Effects of cheerleading practice on advanced glycation end products, areal bone mineral density, and physical fitness in female adolescents - Wang, Lijun; Zhang, Hongli; Xu, Tuo; Zhang, Jing; Liu, Yuanyuan; Qu, Yue (Frontiers in Physiology, 2022)
Background: Exercise has been widely reported to promote bone health, but it is unknown whether is associated with a reduction in advanced glycosylation end products (AGEs). This study aimed to investigate the effects of 14 weeks of cheerleading exercise on areal bone mineral density (aBMD) and AGEs. Methods: In this study, 46 female teenagers (age, 19.52 ± 1.21 years; body mass index, 20.15 ± 2.47 kg/m2) were randomly divided into a cheerleading group (CHE, n = 21) and a control group (CON, n = 25). The CHE group was subjected to cheerleading practice twice a week for 14 weeks; the CON group maintained their daily routine. Dual-energy X-ray absorptiometry was used to measure aBMD, and autofluorescence (AF) values were used to reflect AGEs. Physical fitness testing all-in-one machines are used to test body composition, cardiorespiratory fitness, muscle fitness and flexibility. A mixed ANOVA model was used to examine the effect of the intervention on each outcome. A multiple mediation model with covariates for physical activity and eating behaviors was performed to explore the mediators between cheerleading exercise and aBMD. Results: After 14 weeks of cheerleading practice, 1) aBMD increased significantly in both groups with significantly higher increases in the CHE group (p < 0.05). 2) AGEs significantly decreased in the CHE group (−2.7%), but not in the CON group (p > 0.05). 3) Vertical jumps and sit-ups significantly increased in the CHE group (p < 0.05), but not in the CON group (p > 0.05). 4) ΔAF values was significantly negatively correlated with Δ aBMD (r = −0.302, p < 0.05). 5) ΔAF values mediated the effect of exercise on the aBMD (indirect effect: 0.0032, 95% CI 0.0002–0.0079). Conclusion: Cheerleading practice improved aBMD and physical fitness and reduced AGEs accumulation in female adolescents. The effect of exercise on aBMD was partially mediated by AGEs.